Costly Communion : Ecumenical Initiative and Sacramental Strife in the Anglican Communion - Chapman, Mark D.,; Bonner, Jeremy, (Anglican-Episcopal Theology and History, 2019)
Costly Communion: Ecumenical Initiative and Sacramental Strife in the Anglican Communion seeks to engage with Anglicanism's theological responses to the onset of the twilight of empire and to explore the diversity of Anglican sacramental and ecumenical controversies during the twentieth century. From sacramental initiation and the doctrine of Eucharistic sacrifice to church order and the historic episcopate, Costly Communion offers insights into Anglo-Catholic and Evangelical attempts to resolve the divisions provoked by the impact of the Oxford Movement from the 1830s. In its engagement with sub-Saharan African contextualization of the Anglican, moreover, Costly Communion analyses the unanticipated threat that Anglican diversity now poses for the unity of the Anglican Communion. Contributors are: Jeff Boldt, Jeremy Bonner, Hugh Bowron, Mark Chapman, Colin Buchanan, Ken Farrimond, Joseph Galgalo, Benjamin Guyer, Charlotte Methuen, Thomas Mhuriro, Esther Mombo, Zablon Nthamburi, Kevin Ward.